Prototype of Fire Detection Tool Using Short Message Service (SMS) Notification as A Disaster Mitigation Effort Against Environmental Damage Due to Forest Fires - Aep Setiawan; Akmal Yusup; Amir Machmud (International Journal of Hydrological and Environmental for Sustainability, 2022)
In relation to the threat of drought, it is necessary to do a drought analysis to evaluate the drought that has occurred. Another disaster caused by water drought is forest fires. The purpose of this study using the prototype of a Forest Fire Detection Tool (FFDT) are to early detection of forest fires and providing Short Message Service (SMS) notification of forest fires to the officer. The method of this study used a prototype of a FFDT with SMS Notification. This tool is controlled using the ATmega328 microcontroller or better known as Arduino Uno R3 and also the GSM 800L v2 module so that this tool will provide notification to forest guards in the form of sirens and SMS sounds when there are indications of smoke or fire that are identical to the event of a forest fire. Monitoring uses fire sensors, namely fire for the detection of flames that are often associated with forest fires and uses sensors as soon as possible, namely MQ2 and MQ9, all of which are equipped in one device, a forest fire detector using the Arduino Mega microcontroller. When there is a good sign that the flame or as soon as possible is read, the tool will send an SMS notification to the forest officer, the process of sending the SMS makes the fire process can detect even though it is still in a small condition or not widened.